2018
DOI: 10.1155/2018/8430123
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor and Interleukin-1β Modulate Synaptic Plasticity during Neuroinflammation

Abstract: Cytokines are constitutively released in the healthy brain by resident myeloid cells to keep proper synaptic plasticity, either in the form of Hebbian synaptic plasticity or of homeostatic plasticity. However, when cytokines dramatically increase, establishing a status of neuroinflammation, the synaptic action of such molecules remarkably interferes with brain circuits of learning and cognition and contributes to excitotoxicity and neurodegeneration. Among others, interleukin-1β (IL-1β) and tumor necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 101 publications
0
118
0
3
Order By: Relevance
“…Accumulating evidence indicates that TNFR-mediated TNF-α signaling is a key regulator of neuronal plasticity [61][62][63], particularly of synaptic scaling, which regulates the excitatory drive during chronic inactivity or hyperactivity [64,65]. In addition, evidence from preclinical studies indicates that activation of TNFR1 mainly leads to apoptosis and inflammation, whereas, in contrast, TNFR2 signaling mediates a homeostatic effect, including cell survival and regeneration [65,66]. While studies have documented that there is a complex interaction between TNFR1 and TNFR2, which seems to depend on many contextual factors (e.g., cell type, intracellular or extracellular environment), a reduction of TNFR1 activity within the context of preserved TNFR2 signaling could also shift the balance in favor of cellular survival [63,[67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that TNFR-mediated TNF-α signaling is a key regulator of neuronal plasticity [61][62][63], particularly of synaptic scaling, which regulates the excitatory drive during chronic inactivity or hyperactivity [64,65]. In addition, evidence from preclinical studies indicates that activation of TNFR1 mainly leads to apoptosis and inflammation, whereas, in contrast, TNFR2 signaling mediates a homeostatic effect, including cell survival and regeneration [65,66]. While studies have documented that there is a complex interaction between TNFR1 and TNFR2, which seems to depend on many contextual factors (e.g., cell type, intracellular or extracellular environment), a reduction of TNFR1 activity within the context of preserved TNFR2 signaling could also shift the balance in favor of cellular survival [63,[67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…The application of LPS in high doses in vivo and in vitro decreases the magnitude of LTP [4,19], most likely through an increase in pro-inflammatory cytokines [20]. It has been shown that LTP can either be promoted or prevented through the interference of TNF-α and IL-1β in the pathways controlling the molecular and structural synaptic changes indicative of LTP [20]. A significant increase in IL-1β levels inhibits synaptic strength and LTP in rat [21] and mouse [22] hippocampal slices.…”
Section: Introductionmentioning
confidence: 99%
“…Although various proinflammatory and anti-inflammatory molecules can regulate synaptic plasticity in MS [ 39 ], we focused on the proinflammatory cytokine IL-1β which has been previously identified as one of the main determinants of the inflammatory synaptopathy in MS [ 40 ]. However, a wider set of CSF molecules should be analyzed to better explore the impact of the inflammatory milieu on synaptic functioning, and additional preclinical investigations are needed to clarify the pathophysiological mechanisms of IL-1β-driven synaptic alterations.…”
Section: Discussionmentioning
confidence: 99%